Technology and Manufacturing Process Selection The Product Life Cycle Perspective - Henriques, Elsa.; Henriques, Elsa.; Pecas, Paulo.; Pecas, Paulo.; Silva, Arlindo.; Silva, Arlindo. (Springer Series in Advanced Manufacturing,, 2014)
This book provides specific topics intending to contribute to an improved knowledge on Technology Evaluation and Selection in a Life Cycle Perspectives. Although each chapter will present possible approaches and solutions, there are no recipes for success. Each reader will find his/her balance in applying the different topics to his/her own specific situation. Case studies presented throughout will help in deciding what fits best to each situation, but most of all any ultimate success will come out of the interplay between the available solutions and the specific problem or opportunity the reader is faced with.